PERFORMANCE ANALYSIS OF NON-SIGNALIZED INTERSECTIONS: A CASE OF INTERSECTION OF JALAN KARTINI - MAJALENGKA - Nurmala Dwiani; Mulia Pamadi (Fakultas Teknik Sipil dan Perencanaan, 2024)
As the number of transport increases, the congestion and accidents on the highway increase. Accidents or traffic jams can be caused by an intersection, especially at unsignalized intersections. In Indonesia, accidents and vehicles continue to increase, especially at intersections. Apart from growing accidents, density is also increasing due to increasing or increasing human activity. Research at unsignalized intersections is carried out to prevent increased density and ensure traffic conditions run smoothly. The location of the study to be carried out is at an unsignalized intersection in the Majalengka district. The method used in this research is quantitative, and the data collection technique used is by entering primary and secondary data. Four-way intersection This round has four approaches, each with two paths. The results obtained from calculating traffic volume by conducting direct surveys in the field for three days are divided into two: total flow volume and flow volume of main roads and minor roads. The essential capacity (C0) obtained at a four-way intersection Babakan is 2/2 UD, 2900. Meanwhile, the level of service at the intersection depends on the degree of saturation obtained from the traffic flow value divided by the load capacity. In the previous chapter, the value of the degree of saturation in the north, east, west, and south directions is very high, causing the level of service to be poor. The research results can be used to conclude that the level of service at the four-way intersection Babakan will be more optimal if the load capacity can be increased so that the degree of saturation is low and does not cause high traffic jams.